Timon of Athens - Shakespeare, William, 1564-1616.; Oliver, H. J., (Harold James) (London : AS, 2001)
Presents the text of Shakespeare's "Timon of Athens," in which Timon, beset by financial difficulties and with no one to help him, takes up residence in a cave where he finds buried treasure. Includes notes and commentary, and an introductory essay.
Includes bibliographical references.
Young Adult
Keywords: Timon of Athens (Legendary character) -- Drama; Timon of Athens (Legendary character) -- Drama; Tragedies